The Newfoundland and Labrador Bariatric Surgery Cohort Study: Rational and Study Protocol. Issue 1 (December 2016) - Twells, Laurie; Gregory, Deborah; Midodzi, William; Dillon, Carla; Kovacs, Christopher; MacDonald, Don; Lester, Kendra; Pace, David; Smith, Chris; Boone, Darrell; Murphy, Raleen
Abstract Background In Canada, there has been a disproportionate increase in adults with Class II (BMI 35.0–39.9 kg/m2 ) or Class III obesity (BMI ≥ 40 kg/m2 ) affecting 9 % of Canadians with increases projected. Individuals affected by severe obesity (BMI ≥ 35) are at increased risk of high blood pressure, cardiovascular disease, diabetes, cancer, impaired quality of life, and premature mortality. Bariatric surgery is the most effective treatment for severe obesity. Laparoscopic sleeve gastrectomy (LSG), a relatively new type of bariatric surgery, is growing in popularity as a treatment. The global prevalence of LSG increased from 0 to 37.0 % between 2003 and 2013. In Canada and the US, between 2011 and 2013, the number of LSG surgeries increased by 244 % and LSG now comprises 43 % of all bariatric surgeries. Since 2011, Eastern Health, the largest regional health authority in Newfoundland and Labrador (NL), Canada has performed approximately 100 LSG surgeries annually. Methods A population-based prospective cohort study with pre and post surgical assessments at 1, 3, 6, 12, 18, 24 months and annually thereafter of patients undergoing LSG. This study will report on short - to mid-term (2–4 years) outcomes. Patients (n = 200) followed by the Provincial Bariatric Surgery Program between 19 and 70 years of age, with a BMI between 35.0 and 39.9 kg/m2 and an obesity-related comorbidity or with a BMI ≥ 40 kg/m2 are enrolled. The study is assessing the following outcomes: 1) complications of surgery including impact on nutritional status 2) weight loss/regain 3) improvement/resolution of comorbid conditions and a reduction in prescribed medications 4) patient reported outcomes using validated quality of life tools, and 5) impact of surgery on health services use and costs. We hypothesize a low complication rate, a marked reduction in weight, improvement/resolution of comorbid conditions, a reduction in related medications, improvement in quality of life, and a decrease in direct healthcare use and costs and indirect costs compared to pre-surgery. Discussion Limited data on the impact of LSG as a stand-alone procedure on a number of outcomes exist. The findings from this study will help to inform evidence-based practice, clinical decision-making, and the development of health policy.